The Effect of Social Distancing on Spreading of COVID-19: A Modelling Approach - Saikh, Aktar; Gazi, Nurul Huda (Discontinuity, Nonlinearity, and Complexity, 2026)
Social distancing is a leading concern to the infectious COVID-19 outbreak or any other epidemic diseases which are spreading through the close contact or droplet transmission between a susceptible and infected person. An SIR model is introduced to describe the disease dynamics of the closed cases of Iran as of 31 March 2020. As the pandemic is going on, it is difficult to discuss more insights. We have tried to show the effect of social distancing on the spreading of COVID-19. The study reveals that the well maintains of social or physical distancing reduces the number of infections and deaths due to COVID-19.